2013
DOI: 10.1007/s10584-013-0822-4
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on global agriculture

Abstract: Based on predicted changes in the magnitude and distribution of global precipitation, temperature and river flow under the IPCC SRES A1B and A2 scenarios, this study assesses the potential impacts of climate change and CO 2 fertilization on global agriculture. The analysis uses the new version of the GTAP-W model, which distinguishes between rainfed and irrigated agriculture and implements water as an explicit factor of production for irrigated agriculture. Future climate change is likely to modify regional wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(164 citation statements)
references
References 43 publications
2
154
0
8
Order By: Relevance
“…In these analyses, theoretical adaptations are introduced in order to estimate the degree to which impacts might be moderated by widespread adjustments in crops or land use. For instance, assuming the amount of irrigated land in sub-Saharan Africa were doubled by 2050 (keeping total crop area constant), cereal production would increase by 5 % (Calzadilla et al 2010). Other research has shown that aggregated mean crop yields are expected to decrease by 6-24 % in sub-Saharan Africa, depending on the climate scenario and the type of crop management (e.g., single cropping vs. sequential cropping) used by farmers (Waha et al 2013).…”
Section: Climate Change Impacts Vulnerability and Adaptation (Iva)mentioning
confidence: 99%
“…In these analyses, theoretical adaptations are introduced in order to estimate the degree to which impacts might be moderated by widespread adjustments in crops or land use. For instance, assuming the amount of irrigated land in sub-Saharan Africa were doubled by 2050 (keeping total crop area constant), cereal production would increase by 5 % (Calzadilla et al 2010). Other research has shown that aggregated mean crop yields are expected to decrease by 6-24 % in sub-Saharan Africa, depending on the climate scenario and the type of crop management (e.g., single cropping vs. sequential cropping) used by farmers (Waha et al 2013).…”
Section: Climate Change Impacts Vulnerability and Adaptation (Iva)mentioning
confidence: 99%
“…However, once again some studies [15,16] question the real world benefits of CO2 fertilization, and call into question the results of earlier economic impact studies. Calzadilla [22] found that global food production and GDP will fall as a result of climate change. In the United States, the economic impacts of climate change on agriculture have been projected to likely be negative [23].…”
Section: Agricultural Impacts From Climate Changementioning
confidence: 99%
“…Since European producers are by tendency less harmed by climate change and therefore irrigation costs, one may expect that world prices increase due to climate change more than production costs in Europe (Anderson and Valenzuela 2011;Calzadilla et al 2010). This would generally give the opportunity to European farmers to pass through additional irrigation costs.…”
Section: Cost Sharingmentioning
confidence: 99%